PENGARUH BUDAYA DUKUNGAN KELUARGA TERHADAP KESEIMBANGAN KEHIDUPAN KERJA (STUDI PADA KARYAWAN WANITA YANG SUDAH MENIKAH DI KOTA BANDUNG) - Syifa Nuur Mustika; Meily Margaretha (Departemen Manajemen, 2023)
This study aimed to examine the effect of family support culture on work-life balance for married female employees in the city of Bandung. The sample used in this study were 145 married female employees from various fields of work, the data analysis used in this study was simple regression. Based on the results of the validity and reliability tests of the thirty indicators that have been tested, in the validity test found that there are invalid five variables while in the reliability test all variables are said to be reliable. Therefore, it can be concluded that family support culture has an effect toward work-life balance by 28.3%. Based on the results of the research, companies should give time to their employees to share stories about their families in the company environment during breaks. In addition, companies can carry out promotions so that employees are more active to work and give the best for their work, moreover, the companies should provide opportunities for employees to have special time with their families such as giving time to employees during office days to do their work at home.